Innovations in insuring the poor: Innovations in health insurance: Community-based models - Jütting, Johannes (International Food Policy Research Institute, 2009)
Helping households manage the risks they face is important in reducing poverty in developing countries. All households face health risks, and when health shocks occur, they have a severe impact on people’s livelihoods. High costs of treatment are often exacerbated by reduced income due to ill health. In some cases, people must also sell productive assets to pay for medical care. An estimated 1.3 billion people lack access to effective and affordable healthcare. Publicly funded healthcare, in its current form, is an inadequate mechanism for reaching the poor in many countries, in part because most states have limited health budgets. In two-thirds of all low-income countries, one-third of total health expenditures come directly from patients. Although developing countries bear 93 percent of the world’s disease burden, people in most of these countries still have few options for insuring against health risks. The disease burden is highly concentrated in low-income groups, and most households have little disposable income to spend on healthcare coverage. Institutional innovations in recent years have begun to address issues of coping with health risks and financing healthcare.